1998
DOI: 10.1111/j.1471-0528.1998.tb10259.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised placebo controlled trial of oral misoprostol in the third stage of labour

Abstract: Objective To compare oral misoprostol 400 pg with placebo in the routine management of the Design A double-blind placebo controlled trial. Setting The labour ward of an academic hospital in Johannesburg, South Africa with 7000Participants Low-risk women expected to deliver vaginally. Methods Women in labour were randomly allocated to receive either misoprosto1400 pg orally or placebo after the birth. Conventional oxytocics were given immediately if blood loss was thought to be more than usual. Postpartum blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Mean rise of temperature was more than 0.10 F and statistically significant. Earlier investigations have also reported pyrexia with Misoprostol for first trimester abortion and in the third stage management 16 . Shivering was not known to be a side effect of Misoprostol prior to its use it for the 3 rd stage of labour.…”
Section: Discussionmentioning
confidence: 89%
“…Mean rise of temperature was more than 0.10 F and statistically significant. Earlier investigations have also reported pyrexia with Misoprostol for first trimester abortion and in the third stage management 16 . Shivering was not known to be a side effect of Misoprostol prior to its use it for the 3 rd stage of labour.…”
Section: Discussionmentioning
confidence: 89%
“…The frequency of some adverse effects in the two medication groups of intravenous oxytocin (900 subjects) and oral misoprostol tablet (900 subjects). [11,12]. In a randomised controlled comparison between orally administered misoprostol and standard management in Universitty College Hospital, London, El-Refaey et al, (2000) concluded that many side effects were less common with misoprostol but shivering and pyrexia were more common.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty of the included studies were RCTs, [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] while the remaining 14 were NRS, 9,10,57-67 and together involved a total of 74 204 participants. Most of the NRS were prospective cohort studies, with sample sizes ranging from 400 to 34 631 participants.…”
Section: Included Studiesmentioning
confidence: 99%